INTEGRASI TEKNOLOGI DAN NILAI ISLAM DALAM TRANSFORMASI MANAJEMEN PENDIDIKAN MADRASAH - Mufassir Alam (Hikmah: Journal of Islamic Studies, 2025)
AbstractThis study aims to examine the transformation process of educational management at Madrasah Aliyah Istiqlal Jakarta in responding to the challenges of the digital era. The transformation is carried out as a response to the rapid development of information technology, which requires educational institutions to adapt swiftly and effectively. The research employs a qualitative approach using data collection techniques such as observation, interviews, and documentation. The findings reveal that Madrasah Aliyah Istiqlal has implemented various innovations in educational management, including the integration of technology in the learning process, enhancement of teachers' digital competencies, and the provision of supporting facilities such as multimedia rooms and computer laboratories. Although there are still obstacles, such as limited internet access and shared facility usage schedules, these transformation efforts demonstrate the schoolâ€™s strong commitment to creating a modern, adaptive learning environment aligned with 21st-century educational needs. Therefore, the transformation of educational management at Madrasah Aliyah Istiqlal Jakarta serves as a model of best practices in developing a digital-based madrasah that upholds Islamic values.AbstrakPenelitian ini bertujuan untuk mengkaji proses transformasi manajemen pendidikan Madrasah Aliyah di Madrasah Istiqlal Jakarta dalam menghadapi tantangan era digital. Transformasi dilakukan sebagai respon terhadap perkembangan teknologi informasi yang menuntut lembaga pendidikan untuk beradaptasi secara cepat dan efektif. Metode penelitian yang digunakan adalah pendekatan kualitatif dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa Madrasah Aliyah Istiqlal telah melakukan sejumlah inovasi dalam manajemen pendidikan, meliputi integrasi teknologi dalam proses pembelajaran, peningkatan kompetensi guru di bidang digital, serta penyediaan sarana pendukung seperti ruang multimedia dan laboratorium komputer. Meski masih terdapat kendala, seperti akses internet yang terbatas dan sistem penggunaan fasilitas yang bergiliran, upaya transformasi ini membuktikan komitmen madrasah dalam menciptakan lingkungan belajar yang adaptif, modern, dan relevan dengan kebutuhan peserta didik di abad ke-21. Dengan demikian, transformasi manajemen pendidikan di Madrasah Aliyah Istiqlal Jakarta menjadi contoh praktik baik dalam membangun madrasah berbasis digital yang tetap menjunjung nilai-nilai keislaman.Â